The Effect of Irrigation Techniques on Sustainable Water Management for Rice Cultivation System - A Review - Bittawat Wichaidist; Amornrat Intrman; Songsak Puttrawutichai; Chawakorn Rewtragulpaibul; Supatchaya Chuanpongpanich; Chaisri Suksaroj (Applied Environmental Research, 2023)
Rice serves as a fundamental sustenance for approximately half of the global population, particularly in Asia. Nevertheless, the cultivation of rice demands a substantial water supply, and the challenges associated with water deficits have been exacerbated by irregular rainfall patterns induced by global warming. Consequently, there is a critical need to reassess irrigation techniques to effectively tackle these issues. In this comprehensive review, the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) method was employed to systematically explore literature on irrigation techniques aimed at fostering sustainable water management in rice cultivation systems. The primary components of the framework encompass water consumption and water-related characteristics, soil-related characteristics, and plant-related characteristics, encompassing relevant components and indicators. Two alternative irrigation methods, namely alternate wetting and drying (AWD) and saturated soil irrigation (SSI), have been proposed to enhance water use efficiency (WUE) in rice cultivation compared to traditional continuous flooding (CF). These alternative irrigation methods do not adversely affect rice yield, both quantitatively and qualitatively. Furthermore, these alternative irrigation approaches have the potential to mitigate greenhouse gas (GHG) emissions, particularly methane emissions, in rice production. This review underscores the significance of data on alternate irrigation systems, providing valuable insights for researchers and policymakers in formulating strategies that align at every level for practical implementation. This is crucial as it is relevant to multiple organizations and stakeholders. Moreover, in the face of inclement weather conditions resulting from climate change, the study's findings indicate that research on farmers' adaptation, plant stress, and resilience within the rice cultivation system is still in its nascent stages. This highlights the pressing need for further exploration and advancement in these areas to develop effective strategies for coping with the challenges posed by climate change.